Rotator cuff tear with scapular dyskinesis treated with a pectoralis major transfer and rotator cuff repair: a case report. Issue 5 (17th May 2022) - Figueras, Jorge H; Sabbagh, Ramsey S; Thomson, Cameron G; Shah, Nihar S; Kuechly, Henry A; Mennenga, Ashley; Grawe, Brian
Abstract: We report a 45-year-old man who presented with a rotator cuff tear and scapular dyskinesis of his left shoulder and underwent a pectoralis major split transfer with an allograft to the inferior border of his scapula. The patient reported significant improvement in shoulder function and decreased severity of his scapular dyskinesis. Combined arthroscopic rotator cuff repair and allograft scapula stabilization is a novel technique for the unusual clinical presentation reported in this case report. To the best of our knowledge, this is the first reported surgical management of a patient with rotator cuff repair and non-palsy-related scapular dyskinesis.